การพัฒนาเกณฑ์อ้างอิงสําหรับการจัดหาระบบสารสนเทศหน่วยงานของรัฐ - อุตตรนที, ฑกลชัย; ชูกิตติกุล, จารึก; ชินะตระกูล, สมชัย; ชูกิตติกุล, วจี (JOURNAL OF SOUTHERN TECHNOLOGY, 2015)
การวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาเกณฑ์อ้างอิงการจัดหาระบบสารสนเทศหน่วยงานของรัฐ ประกอบด้วยข้อกําหนดความต้องการด้านคุณภาพด้านความมั่นคงปลอดภัย และด้านปัจจัยความสําเร็จ กลุ่มตัวอย่างคือ ผู้มีส่วนเกี่ยวข้องในการจัดหาระบบสารสนเทศหน่วยงานของรัฐจากฝ่ายเทคโนโลยีสารสนเทศ และฝ่ายจัดหาและการพัสดุ จํานวน 111 คน แบ่งเป็นระดับอํานวยการ จํานวน 14 คน ระดับจัดการ จํานวน 31 คน และระดับปฏิบัติการ จํานวน 66 คน เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถาม สถิติที่ใช้วิเคราะห์ข้อมูล ได้แก่ ความถี่ ค่าเฉลี่ย และค่าไค-สแควร์ ผลการวิจัยพบว่า (1) เกณฑ์อ้างอิงการจัดหาระบบสารสนเทศหน่วยงานของรัฐ มีจํานวน 20 ข้อกําหนด ประกอบด้วย ข้อกําหนดความต้องการด้านคุณภาพ จํานวน 6 ข้อ ด้านความมั่นคงปลอดภัยจํานวน 8 ข้อ และด้านปัจจัยความสําเร็จจํานวน 6 ข้อ และ (2) ทดสอบการยอมรับเกณฑ์อ้างอิงการจัดหาระบบสารสนเทศหน่วยงานของรัฐที่พัฒนาขึ้น ผลปรากฏว่าเกณฑ์อ้างอิงการจัดหาได้รับการยอมรับจากผู้มีส่วนเกี่ยวข้องทุกข้อกําหนด โดยมีค่าการยอมรับอยู่ในระดับมาก ทั้งนี้ จํานวนผู้ยอมรับแตกต่างจากจํานวนผู้ไม่ยอมรับอย่างมีนัยสําคัญทางสถิติที่ระดับ .05 ข้อค้นพบในงานวิจัยนี้ คือ เกณฑ์อ้างอิงการจัดหาระบบสารสนเทศหน่วยงานของรัฐที่ได้รับการยอมรับจากผู้มีส่วนเกี่ยวข้อง และนวัตกรรมที่ได้ คือ รูปแบบเกณฑ์อ้างอิงการจัดหาระบบสารสนเทศหน่วยงานของรัฐ ซึ่งสังเคราะห์ขึ้นจากเกณฑ์อ้างอิงการจัดหาจํานวน 20 ข้อกําหนด Developing the Criteria for Procurement of the Government Information System The purpose of this research was to develop the criteria for procurement of the government information system which comprised requirements in terms of a set of quality, security and success factor. The samples were 111 stakeholders involved in the government information system procurement from the Information Technology department and the Procurement department, categorized as 14 directors, 31 managers and 66 staffs. The tool was a set of questionnaires. The statistics used for data analysis were frequency, mean and Chi-square. The results obtained were: (1) The criteria for procurement of the government information system has 20 requirements, comprised 6 quality, 8 security, and 6 success factor requirements. (2) The test of acceptance for the criteria for procurement of the government information system was made by the stakeholders involved in the government information system procurement found that they accepted all requirements and the level of acceptance was in the high level. Also the numbers of acceptors were significantly different from the numbers of deniers at the level of .05 The contribution in this research was the criteria for procurement of the government information system which accepted by the stakeholders and an innovation. The criteria for procurement of the government information system model synthesized from all 20 requirements of the criteria for procurement was obtained.